Banking regulation and prompt corrective action - Xavier Freixas; Bruno Maria Parigi (Center for Economic Studies and ifo Institute (CESifo), 2007)
We explore the rationale for regulatory rules that prohibit banks from developing some of their natural activities when their capital level is low, as epitomized by the US Prompt Corrective Action (PCA). This paper is built on two insights. First, in a moral hazard setting, capital requirement regulation may force banks to hold a large fraction of safe assets which, in turn, may lower their incentives to monitor risky assets. Second, agency problems may be more severe in certain asset classes than in others. Taken together, these two ideas explain why, surprisingly, capital regulation, which may cope with risk and adverse selection, is unable to address issues related to moral hazard. Hence, instead of forcing banks to hold a large fraction of safe assets, prohibiting some types of investment and allowing ample scope of investment on others may be the only way to preserve incentives and guarantee funding. In particular, providing incentives to monitor investments in the most opaque asset classes may prove to be excessively costly in terms of the required capital and thus inefficient. We show that the optimal capital regulation consists of a rule that a) allows well capitalized banks to freely invest any amount in any risky asset, b) prohibits banks with intermediate levels of capital to invest in the most opaque risky assets, and c) prohibits undercapitalized banks to invest in any risky asset.
Keywords: E58; G21; 330; banking; prudential regulation; moral hazard; Bankenpolitik; Investitionsrisiko; Investition; USA; Moral Hazard; Agency Theory; Theorie